Attentional selection and suppression in children and adults. Issue 6 (15th May 2018) - Sun, Meirong; Wang, Encong; Huang, Jing; Zhao, Chenguang; Guo, Jialiang; Li, Dongwei; Sun, Li; Du, Boqi; Ding, Yulong; Song, Yan
Abstract: The fundamental role of covert spatial attention is to enhance the processing of attended items while simultaneously ignoring irrelevant items. However, relatively little is known about how brain electrophysiological activities associated with target selection and distractor suppression are involved as they develop and become fully functional. The current study aimed to identify the neurophysiological bases of the development of covert spatial attention, focusing on electroencephalographic (EEG) markers of attentional selection (N2pc) and suppression (PD ). EEG data were collected from healthy young adults and typically developing children (9–15 years old) as they searched for a shape singleton target in either the absence or the presence of a salient‐but‐irrelevant color singleton distractor. The ERP results showed that a lateral shape target elicited a smaller N2pc in children compared with adults regardless of whether a distractor was present or not. Moreover, the target‐elicited N2pc was always followed by a similar positivity in both age groups. Counterintuitively, a lateral salient‐but‐irrelevant distractor elicited a large PD in children with low behavioral accuracy, whereas high‐accuracy children exhibited a small and "adult‐like" PD . More importantly, we found no evidence for a correlation between the target‐elicited N2pc and the distractor‐elicited PD in either age group. Our results provide neurophysiological evidence for the developmental differences between target selection and distractor suppression. Compared with adults, 9–15‐year‐old children deploy insufficient attentional selection resources to targets but use "adult‐like" or even more attentional suppression resources to resist irrelevant distractors. A video abstract of this article can be viewed at:https://www.youtube.com/watch?v=NhWapx0d75I Abstract : Using a visual search paradigm, we found that, compared with adults, 9–15‐year‐old children deployed insufficient attentional selection resources to targets but used "adult‐like" or even more attentional suppression resources to resist irrelevant distractors.